2020
DOI: 10.21203/rs.3.rs-20139/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using CT texture analysis to differentiate between peripheral lung cancer and pulmonary inflammatory pseudotumor

Abstract: Background: Pulmonary inflammatory pseudotumor (PIPT) usually presents as solitary peripheral well-defined nodules or masses, and CT features are complex and changeable, which are often confused with peripheral lung cancer. This study is to distinguish peripheral lung cancer and PIPT using CT-radiomics features extracted from PET/CT images.Methods: In this study, the standard 18F-fluorodeoxyglucose positron emission tomography/ computed tomography (18 F-FDG PET/CT) images of 21 patients with pulmonary inflamma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…They found 14 of 330 GLCM, 1 of 49 first-order features, and 5 or 18 shape features to fit their criteria. They found that a model using shape features performed the best (64). While the studies are limited, they seem to suggest first order statistics may not have a significant role to play in differentiating benign and malignant nodules compared to features derived from shape and texture features derive from second-and higherorder statistics.…”
Section: Predicting Benign Vs Malignant Nodulesmentioning
confidence: 99%
“…They found 14 of 330 GLCM, 1 of 49 first-order features, and 5 or 18 shape features to fit their criteria. They found that a model using shape features performed the best (64). While the studies are limited, they seem to suggest first order statistics may not have a significant role to play in differentiating benign and malignant nodules compared to features derived from shape and texture features derive from second-and higherorder statistics.…”
Section: Predicting Benign Vs Malignant Nodulesmentioning
confidence: 99%
“…[1]original_shape_VoxelVolume [2]original_shape_Sphericity [3]original_shape_Maximum2DDiameterSlice [4]original_shape_Maximum2DDiameterColumn [5]original_shape_Maximum3DDiameter [6]original_shape_Flatness [7]original_shape_MeshVolume [8]original_shape_SurfaceArea [9]original_shape_MinorAxisLength [10]original_shape_SurfaceVolumeRatio [11]original_shape_Maximum2DDiameterRow [12]original_shape_MajorAxisLength [13]original_shape_LeastAxisLength [14]original_shape_Elongation [15]original_glcm_ClusterProminence [16]original_glcm_SumSquares [17]original_glcm_DifferenceVariance [18]original_glcm_JointAverage [19]original_glcm_Contrast [20]original_glcm_ClusterShade [21]original_glcm_Idm [22]original_glcm_Idmn [23]original_glcm_Id [24]original_glcm_MCC [25]original_glcm_Autocorrelation [26]original_glcm_JointEnergy [27]original_glcm_JointEntropy [28]original_glcm_SumAverage [29]original_glcm_InverseVariance [30]original_glcm_Imc2 [31]original_glcm_ClusterTendency [32]original_glcm_DifferenceAverage [33]original_glcm_DifferenceEntropy [34]original_glcm_SumEntropy [35]original_glcm_Idn [36]original_glcm_MaximumProbability [37]original_glcm_Imc1 [38]original_glcm_Correlation [39]original_ngtdm_Contras [40]original_ngtdm_Strength…”
Section: Supplementarymentioning
confidence: 99%
“…However, this method is invasive and requires random sampling of tumor fragments (7). In contrast, radiomics analysis (8,9) is considered to be a noninvasive tool for the classification of lung cancer histopathological subtypes through medical image analysis, which offers quantitative tumor heterogeneity information (10,11) by quantitatively describing shapes, gray level histograms, or textures (12,13).…”
Section: Introductionmentioning
confidence: 99%